PENGEMBANGAN PRODUK MI INSTAN DARI TEPUNG HOTONG (Setaria italica Beauv.) DAN PENDUGAAN UMUR SIMPANNYA DENGAN METODE AKSELERASI [Development of Instant Noodle Made from Foxtail Millet (Setaria italica Beauv.) Flour and Prediction of Its Shelf Life u - Sugiyono .; Sarwo E. Wibowo; Sam Herodian; Sri Widowati; B.A. Susila Santosa (Jurnal Teknologi dan Industri Pangan, 2010)
The objective of this research was to develop instant noodle products made from foxtail millet flour and to predict their shelf life using acceleration method.  The instant noodle was produced using 30, 35, 40% water, and steaming process for 10, 15, 20 minutes. The best noodle product was achieved with 30% water addition and 10 minutes steaming. The noodle contained 2.33% moisture, 1.86% ash,  9.83% protein, 14.66% fat, and 71.33% carbohydrate. The product had 70.47Hue value, 68.64 whiteness (L), 1641.33 gramforce hardness, 473.43 gramforce stickiness, 160.02% water absorption, 19.38% cooking loss, and 6.5 minutes  rehydration time.  Prediction of the product shelf life using the acceleration method showed that the noodle product had a shelf life of 99.86 days based on its rancidity.